Enrichment Protocol for Rat Models. Issue 6 (8th June 2021) - Ismail, Teh Rasyidah; Yap, Christina Gertrude; Naidu, Rakesh; Pamidi, Narendra
Abstract: An environmental enrichment (EE) cage consisting of a broad living area and various stimulators triggers social, cognitive, and physical activities. EE has been utilized in a wide range of neurological and non‐neurological studies. However, the details of the environmental enrichment protocol were not well described in these studies. This has resulted in uncertainty and inconsistency in methodology, which may thus fail to replicate environmental enrichment effects, influencing the study outcome. Here we describe the basic guidelines and present an easy‐to‐follow protocol for environmental enrichment in rat models. © 2021 Wiley Periodicals LLC. Basic Protocol : Environmental enrichment housing